The Work Place Educational Climate in Gynecological Oncology Fellowships Across Europe: The Impact of Accreditation. Issue 1 (1st January 2015) - Piek, Jurgen; Bossart, Michaela; Boor, Klarke; Halaska, Michael; Haidopoulos, Dimitrios; Zapardiel, Ignacio; Grabowski, Jacek; Kesic, Vesna; Cibula, David; Colombo, Nicoletta; Verheijen, Rene; Manchanda, Ranjit
Abstract : Background: A good educational climate/environment in the workplace is essential for developing high-quality medical (sub)specialists. These data are lacking for gynecological oncology training. Objective: This study aims to evaluate the educational climate in gynecological oncology training throughout Europe and the factors affecting it. Methods: A Web-based anonymous survey sent to ENYGO (European Network of Young Gynecological Oncologists) members/trainees to assess gynecological oncology training. This included sociodemographic information, details regarding training posts, and a 50-item validated Dutch Residency Educational Climate Test (D-RECT) questionnaire with 11 subscales (1–5 Likert scale) to assess the educational climate. The χ 2 test was used for evaluating categorical variables, and the Mann-Whitney U (nonparametric) test was used for continuous variables between 2 independent groups. Cronbach α assessed the questionnaire reliability. Multivariable linear regression assessed the effect of variables on D-RECT outcome subscales. Results: One hundred nineteen gynecological oncological fellows responded. The D-RECT questionnaire was extremely reliable for assessing the educational environment in gynecological oncology (subscales' Cronbach α, 0.82–0.96). Overall, trainees do not seem to receive adequate/effective constructive feedback during training. The overall educational climate (supervision, coaching/assessment, feedback, teamwork, interconsultant relationships, formal education, role of the tutor, patient handover, and overall consultant's attitude) was significantly better ( P = 0.001) in centers providing accredited training in comparison with centers without such accreditation. Multivariable regression indicated the main factors independently associated with a better educational climate were presence of an accredited training post and total years of training. Conclusions: This study emphasizes the need for better feedback mechanisms and the importance of accreditation of centers for training in gynecological oncology to ensure training within higher quality clinical learning climates.